Standard-dose versus double-dose dolutegravir in HIV-associated tuberculosis in South Africa (RADIANT-TB): a phase 2, non-comparative, randomised controlled trial - Griesel, R; Zhao, Y; Simmons, B; Omar, Z; Wiesner, L; Keene, CM; Hill, AM; Meintjes, G; Maartens, G (Elsevier, 2023)
Background The drug–drug interaction between rifampicin and dolutegravir can be overcome by supplemental dolutegravir dosing, which is difficult to implement in high-burden settings. We aimed to test whether virological outcomes with standard-dose dolutegravir-based antiretroviral therapy (ART) are acceptable in people with HIV on rifampicin-based antituberculosis therapy. Methods RADIANT-TB was a phase 2b, randomised, double-blind, non-comparative, placebo-controlled trial at a single site in Khayelitsha, Cape Town, South Africa. Participants were older than 18 years of age, with plasma HIV-1 RNA greater than 1000 copies per mL, CD4 count greater than 100 cells per μL, ART-naive or first-line ART interrupted, and on rifampicin-based antituberculosis therapy for less than 3 months. By use of permuted block (block size of 6) randomisation, participants were assigned (1:1) to receive either tenofovir disoproxil fumarate, lamivudine, and dolutegravir plus supplemental 50 mg dolutegravir 12 h later or tenofovir disoproxil fumarate, lamivudine, and dolutegravir plus matched placebo 12 h later. Participants received standard antituberculosis therapy (rifampicin, isoniazid, pyrazinamide, and ethambutol for the first 2 months followed by isoniazid and rifampicin for 4 months). The primary outcome was the proportion of participants with virological suppression (HIV-1 RNA <50 copies per mL) at week 24 analysed in the modified intention-to-treat population. This study is registered with ClinicalTrials.gov, NCT03851588. Findings Between Nov 28, 2019, and July 23, 2021, 108 participants (38 female, median age 35 years [IQR 31–40]) were randomly assigned to supplemental dolutegravir (n=53) or placebo (n=55). Median baseline CD4 count was 188 cells per μL (IQR 145–316) and median HIV-1 RNA was 5·2 log10 copies per mL (4·6–5·7). At week 24, 43 (83%, 95% CI 70–92) of 52 participants in the supplemental dolutegravir arm and 44 (83%, 95% CI 70–92) of 53 participants in the placebo arm had virological suppression. No treatment-emergent dolutegravir resistance mutations were detected up to week 48 in the 19 participants with study-defined virological failure. Grade 3 and 4 adverse events were similarly distributed between the study arms. The most frequent grade 3 and 4 adverse events were weight loss (4/108 [4%]), insomnia (3/108 [3%]), and pneumonia (3/108 [3%]). Interpretation Our findings suggest that twice-daily dolutegravir might be unnecessary in people with HIV-associated tuberculosis. Funding Wellcome Trust.